The Maqasid of Modern Philanthropy: Deconstructing al-Qardawi’s Istinbat and Its Institutionalization within the Indonesian Zakat Framework - Muhammad Aziz (Akademika, 2026)
The transition toward a globalized service economy has exposed a critical conceptual gap in classical Islamic philanthropy, which historically focused on agrarian wealth and physical commodities. This article investigates the deconstruction of Yusuf al-Qardawi’s istinbat (legal deduction) methodology regarding professional zakat (zakat profesi) and its subsequent institutionalization within the Indonesian legal landscape. Specifically, it addresses three critical analytical dimensions: (1) the jurisprudential reconceptualization of professional income as a modern productive asset under the Maqasid al-Sharia framework; (2) the process of legal transplantation of these reformist ideas into Indonesian Law No. 23 of 2011; and (3) the socio-legal trajectory of shifting from commodity-based to human-capital-based philanthropy. Employing a socio-legal approach and textual hermeneutics, the study deconstructs the logical bridge in al-Qardawi’s Fiqh al-Zakah, identifying growing wealth (al-nama’) as the effective cause (‘illat) that equates intellectual labor with classical gold and silver assets. The findings reveal that this methodology has been successfully institutionalized in Article 4 of Law No. 23/2011, providing definitive legal certainty for the state to manage zakat from modern professional services. This research argues that such methodological flexibility is essential for achieving distributive justice (al-‘adalah al-tawzi’iyyah) and correcting the historical agrarian bias in philanthropic burdens. Ultimately, the study demonstrates that the trajectory of social justice in Indonesian philanthropy is increasingly shaped by the synthesis of reformist jurisprudence and state statutory law